Effectiveness of a program to lower unwanted media screens among 2–5-year-old children: a randomized controlled trial - Kaur, Nimran; Gupta, Madhu; Chakrapani, Venkatesan; Khan, Firoz; Malhi, Prahbhjot; Kiran, Tanvi; Grover, Sandeep (Frontiers in Public Health, 2024)
Background Limited interventions exist on reducing unwanted screen time (ST) among children from low- and middle-income countries (LMICs), so we developed and assessed the effectiveness of the program to lower unwanted media screen time (PLUMS) among children aged 2-5 years in Chandigarh, Union Territory, North India. Methods An open-label randomized control parallel-group trial per CONSORT guidelines was conducted among randomly selected 340 families with children aged 2-5 (±3 months) years in Chandigarh, India. PLUMS was implemented at the family level with a focus on modifying the home media environment and targeted individual-level interventions using parent and child modules for two months. A post-intervention (immediately) and a follow-up assessment after six months was done. During the follow-up period, the interaction was done passively via WhatsApp groups. The control group received routine healthcare services. Validated and standardized tools, including a digital screen exposure questionnaire with a physical activity component, preschool child behavior checklist, and sleep disturbance scale for children, were used to collect data at baseline, post-intervention, and follow-up periods. The primary outcome was the mean difference in ST (minutes/day) among children in the intervention versus the control group. Generalized estimating equation (GEE) analysis was performed to adjust for clustering. Results An equal number of families (n=170) were randomly assigned to the intervention and control arms. In the post-intervention assessment, 161 and 166 families continued while, at the follow-up assessment, 154 and 147 were in the intervention and control arm, respectively. The mean difference in ST on a typical day [27.7 minutes, 95% Confidence Interval (CI) 5.1, 50.3] at the post-intervention assessment significantly (p<0.05) decreased in intervention (102.6±98.5 minutes) as compared to the control (130.3±112.8 minutes) arm. A significant reduction in ST (=-35.81 minutes, CI -70.6, -1.04) from baseline (=123.1 minutes) to follow-up phase (=116 minutes) was observed in GEE analysis. The duration of physical activity increased both at post-intervention (=48.4 minutes, CI=+6.6, +90.3) and follow-up (=73.4 minutes, CI=36.2, 110.5) assessments in the intervention arm. Conclusion The PLUMS intervention significantly reduced the children’s mean ST on a typical day and increased the physical activity immediately post-intervention and during the six-month follow-up period.